2022
DOI: 10.1002/adhm.202200977
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Temperature Printed Hierarchically Porous Induced‐Biomineralization Polyaryletherketone Scaffold for Bone Tissue Engineering

Abstract: Polyetheretherketone (PEEK) as a popular orthopaedic implant is usually fabricated into a hierarchically porous structure for improving osteogenic activity. However, the applications are limited due to the excessively high processing temperature and uncontrollably tedious modification routes. Here, an amorphous polyaryletherketone with carboxyl groups (PAEK-COOH) is synthesized and fabricated to the hierarchically controllable porous scaffolds via a low-temperature 3D-printing process. The prepared PAEK-COOH s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…[39][40][41] After implantation of the bioactive prosthesis, macrophages are recruited to the implantation area [42] and can secrete various scaffold-induced immunomodulatory chemokines that regulate the associated immune response and bone formation. [42][43][44] Further flow cytometry, ELISA, and immunofluorescence results confirmed that the bioactive prostheses promoted the polarization of macrophages toward the M2 phenotype, which may largely be attributed to polyphenolinduced anti-inflammation. [45] Meanwhile, endogenous stem cells were recruited and homed to defective sites, providing good conditions for mature bone tissues.…”
Section: Discussionmentioning
confidence: 74%
“…[39][40][41] After implantation of the bioactive prosthesis, macrophages are recruited to the implantation area [42] and can secrete various scaffold-induced immunomodulatory chemokines that regulate the associated immune response and bone formation. [42][43][44] Further flow cytometry, ELISA, and immunofluorescence results confirmed that the bioactive prostheses promoted the polarization of macrophages toward the M2 phenotype, which may largely be attributed to polyphenolinduced anti-inflammation. [45] Meanwhile, endogenous stem cells were recruited and homed to defective sites, providing good conditions for mature bone tissues.…”
Section: Discussionmentioning
confidence: 74%
“…A compression modulus enhancement of approximately 186% (252.91 MPa) and yield strength enhancement of 43% (4.51 MPa) was observed when only 0.5 wt.% CNTs were added to PEEK/HA. Using a low-temperature 3D printing process, Gao et al [ 28 ] fabricated amorphous PAEK with carboxyl groups (PAEK-COOH) into hierarchically controllable porous scaffolds from the nanoscale to the microscale, with a mechanical strength comparable to that of trabecular bone. The nanoporous surface of the PAEK-COOH scaffold is beneficial in promoting cell adhesion, whereas the carboxyl groups can induce HA mineralization through electrostatic interactions.…”
Section: Mechanical Properties Of Peek In Dental Applicationsmentioning
confidence: 99%
“…PAEK-COOH was synthesized via nucleophilic substitution poly-condensation reaction (Figure 1a) from phenolphthalin (PPH) and 4, 4'-difluorobenzophenone (DFBP) in dimethyl sulfoxide (DMSO), with potassium carbonate (K 2 CO 3 ) as the catalyst. [22] Analysis by 1 H nuclear magnetic resonance (NMR) and fourier-transformed infrared (FT-IR) spectrum can confirm the presence of ether bonds, carbonyl, and carboxyl groups (Figures S1 and S2, Supporting Information). As reported, EDC can greatly improve the reactivity of carboxyl groups.…”
Section: Synthesis and Characterization Of Compositesmentioning
confidence: 99%